Efeitos dos recursos de baixa tecnologia assistiva nas atividades lúdicas para crianças com paralisia cerebral na educação infantil - Zuttin, Fabiana da Silva (Universidade Federal de São Carlos, 2010)
Playing is considered a natural and basic process for the development of some abilities in infancy. However, children with physical deficiency, such as children with cerebral palsy, for presenting a disorder on the muscular tonus and on the posture, may have difficulties in carrying through this playful experience in many contexts, especially in school environment. In the current time, for many of these children, it is possible to create a facilitator environment of this process of playing through the use of resources of assistive technology. In this perspective, the present study had the objective to elaborate and implement individualized programs of intervention based on playful activities, coming from the knowledge of the Occupational Therapy and to evaluate its effect. The related individualized programs had been supported in resources of low assistive technology for the participation of children with cerebral palsy in the school context of the kindergarten. Three children with the diagnosis of Cerebral Palsy, of the spastic type, enrolled in a private regular education of the kindergarten, in a medium size city of Sao Paulo state and its respective professors, participated in this study. The instruments used for the collection of data were: a script of interview for the professors on the participation of its pupils in the playful activities in Kindergarten (REPPAAL-EI) and the Canadian Occupational Performance Measure (COPM) used as indirect measurement. Both were applied for the professors and the Protocol of the Playful Model, as direct measurement in order to observe the child with cerebral palsy in the playful activities of the kindergarten. The results demonstrated that the intervention program promoted improvement in the performance of the children in relation of the participation on the playful activities in the school context, corroborating with the objective of the current research. Moreover, it promoted benefits that made it easier the process of inclusion of these children in school environments.
Keywords: Brincar; Recursos adaptados; Deficiência física; Recursos de baixa tecnologia assistiva; Educação infantil; Paralisia cerebral; Playing; Resources of low assistive technology; Kindergarten; Cerebral palsy; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL